2021
DOI: 10.3390/ijerph18020794
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Anxiety—A Longitudinal Survey Study of Psychological and Situational Risks among Finnish Workers

Abstract: Background: The COVID-19 crisis has changed the conditions of many all over the globe. One negative consequence of the ongoing pandemic is anxiety brought about by uncertainty and the COVID-19 disease. Increased anxiety is a potential risk factor for wellbeing at work. This study investigated psychological, situational, and socio-demographic predictors of COVID-19 anxiety using longitudinal data. Methods: A nationally representative sample of Finnish workers (N = 1308) was collected before and during the COVID… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 66 publications
8
63
1
Order By: Relevance
“…Studies that examined the effect of COVID-19 pandemic on working population were mostly focused on healthcare workers as one of the most vulnerable groups (Gasparro et al, 2020;Giorgi et al, 2020;Mattila et al, 2021). One study in general working population in Finland has shown that COVID-19 anxiety was associated with perceived loneliness, neuroticism, distress (Savolainen et al, 2021). There is an evident lack of information how workers in different professions and those with more unstable job and income situation are dealing with all changes and uncertainty during a COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined the effect of COVID-19 pandemic on working population were mostly focused on healthcare workers as one of the most vulnerable groups (Gasparro et al, 2020;Giorgi et al, 2020;Mattila et al, 2021). One study in general working population in Finland has shown that COVID-19 anxiety was associated with perceived loneliness, neuroticism, distress (Savolainen et al, 2021). There is an evident lack of information how workers in different professions and those with more unstable job and income situation are dealing with all changes and uncertainty during a COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…which were rated on a 3-point scale (1 = hardly ever, 3 = often). The scale was previously used to study loneliness during COVID-19 [17].…”
Section: Methodsmentioning
confidence: 99%
“…It contained three items (“How often do you feel lonely?”, “How often do you feel left out?”, “How often do you feel isolated from others?”) which were rated on a 3-point scale (1 = hardly ever, 3 = often). The scale was previously used to study loneliness during COVID-19 [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations